Gap analysis of future studies on wildlife tourism in Lower Kinabatangan, Sabah - King , Natalie; Nair, Vikneswaran (2013)
The value of wildlife as consumptive or non-consumptive ecotourism activities are evident in many research carried out in the field of wildlife tourism. The Batuh Puteh (Orang Sungai) community of Lower Kinabatangan, Sabah has successfully adopted a combination of an ‘authentic’ vacation where tourists are open to new cultures and experiencing the natural endowment in the form of non-consumptive wildlife tourism activities. Hence, the objective of this paper is to determine the world-wide view on the concept of wildlife tourism and what are the gaps of future studies in this field for a destination that is known for wildlife tourism. Information for the study was gathered from case studies and articles from a selection of countries based on the notability of their wildlife tourism ventures. The analysis of these cases will be used to review and propose recommendations for further research in the Lower Kinabatangan, Sabah. The suggestions of sustainability, Stakeholder Corporation, biodiversity management, ethical nature values and environmental education and awareness are particularly important to wildlife tourism researchers and decision makers. The analysis from the literature will be useful in finding the gaps of future studies on wildlife tourism in Malaysia with specific reference to Lower Kinabatangan, Sabah.